E-LEARNING DALAM PEMBELAJARAN - Ade Kusmana (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2011)
This article deals the e-learning and how it develops. E-learning system is badly needed to keep up with the development supported by information technology leading to digital era both pro-cess and content. To develop an e-learning system, it should be pre-ceded by a user-need analysis. In line with the paradigm of planned system and software, the user-need analysis is of great importance as it is a basis of design. These are designed to avoid a bad implementa-tion process of e-learning system, which mainly due to the irrelevance of developed system to the real need of users.